The Influence of Principal and School’s Committee Leadership on the Implementation of School-Based Management - Kaimudin, Kaimudin; Ahyani, Nur; Wahidy, Achmad (Journal of Social Work and Science Education, 2024)
This study aims to determine the influence of the leadership of the school principal and school committee on the implementation of school-based management in SD Negeri Se Gugus 1, Lubuk Besar District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all teachers consisting of 106 teachers at SD Negeri Se Cluster 1, Lubuk Besar District. data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant influence between the principal's leadership on school-based management of Cluster 1 Public Elementary Schools, Lubuk Besar District; 2) there is a significant influence of the school committee on school-based management of Cluster 1 Public Elementary Schools in Lubuk Besar District; 3) There is a significant influence jointly on the leadership of the school principal and the school committee on the school-based management of Cluster 1 Public Elementary Schools, Lubuk Besar District.